Teaching methods and types of games in teaching Turkish as a foreign language - Бaлтaбaевa Д.,; Урaзбековa Р. (Journal of Oriental Studies, 2017)
This article investigates methods of teaching new words of Turkish language by learning as association by drawing shapes and pictures on board are shown which is motivated of training foreign language. And also it is considered importance and role training games in studying of the Turkish language of foreign students.